Coming of a precision era of the staging systems for intrahepatic cholangiocarcinoma?. (28th September 2019) - Cheng, Zhangjun; Lei, Zhengqing; Shen, Feng
Abstract: Intrahepatic cholangiocarcinoma (ICC) is the second most common primary liver cancer. Appropriate treatment of this aggressive and heterogeneous cancer requires accurate staging and prognostic stratification, as does patient selection for clinical trials. Over the past two decades, several staging systems and prognostic models for ICC have been developed. Most include independent prognostic factors such as tumor extent, clinical parameters and histopathological features and are inaccurate. Accumulating findings offer new insights into the genetic and molecular basis of ICC progression. Hence, staging systems and prognostic models that incorporate in clinicalpathological factors, molecular and genomic information, and tumor biomarkers, and hence more accurately estimate prognosis, will become a reality. This review summarizes the current staging systems and prognostic models for ICC and highlights the need to establish more precise and personalized systems and models that incorporate tumor biologic factors. Highlights: Intrahepatic cholangiocarcinomas are aggressive and highly heterogeneous. Accurate staging and risk stratification are important for treatment selection. Traditional staging systems and prognostic models are imprecise. Including of molecular and genetic information in these models would improve accuracy.